The arts across curriculum - Jissel Arroyo, Jorge A. López (Revista de Orientación Educacional, 2023)
We examine the effect of using art to improve the learning of social studies. The study focuses on a group of 4th graders, Hispanic, not English proficient, lacking in interest in social studies. The instruments used are: A Parent-Teacher Interview, the Student’s Writing/Social Studies/Arts Survey, an open-ended survey, and the collected data from the Texas Essential Knowledge and Skills practice test. We find that incorporating arts in content areas provides opportunities for students to succeed in school, develop their self-esteem, and increase the students' interest for the arts.